Rifampin Regulation of Drug Transporters Gene Expression and the Association of MicroRNAs in Human Hepatocytes - Benson, Eric A.; Eadon, Michael T.; Desta, Zeruesenay; Liu, Yunlong; Lin, Hai; Burgess, Kimberly S.; Segar, Matthew W.; Gaedigk, Andrea; Skaar, Todd C. (Frontiers in Pharmacology, 2016)
Membrane drug transporters contribute to the disposition of many drugs. In human liver, drug transport is controlled by two main superfamilies of transporters, the solute carrier transporters (SLC) and the ATP Binding Cassette transporters (ABC). Altered expression of these transporters due to drug-drug interactions can contribute to differences in drug exposure and possibly effect. In this study, we determined the effect of rifampin on gene expression of hundreds of membrane transporters along with all clinically relevant drug transporters. Methods: In this study, primary human hepatocytes (n=7 donors) were cultured and treated for 24 hours with rifampin and vehicle control. RNA was isolated from the hepatocytes, mRNA expression was measured by RNA-seq, and miRNA expression was analyzed by Taqman OpenArray. The effect of rifampin on the expression of selected transporters was also tested in kidney cell lines. The impact of rifampin on the expression of 410 transporter genes from 19 different transporter gene families was compared with vehicle control. Results: Expression patterns of 12 clinically relevant drug transporter genes were changed by rifampin (FDR<0.05). For example, the expressions of ABCC2, ABCB1, and ABCC3 were increased 1.9-, 1.7-, and 1.2- fold, respectively. The effects of rifampin on four uptake drug transporters (SLCO1B3, SLC47A1, SLC29A1, SLC22A9) were negatively correlated with the rifampin effects on specific microRNA expression (SLCO1B3/miR-92a, SLC47A1/miR-95, SLC29A1/miR-30d#, and SLC22A9/miR-20; r<-0.79; p<0.05). Seven hepatic drug transporter genes (SLC22A1, SLC22A5, SLC15A1, SLC29A1, SLCO4C1, ABCC2, and ABCC4), whose expression was altered by rifampin in hepatocytes, were also present in a renal proximal tubular cell line, but in renal cells rifampin did not alter their gene expression. PXR expression was very low in the kidney cells; this may explain why rifampin induces gene expression in a tissue-specific manner. Conclusion: Rifampin alters the expression of many of the clinically relevant hepatic drug transporters, which may provide a rational basis for understanding rifampin-induced drug-drug interactions reported in vivo. The relevance of its effect on many other transporters remains to be studied.